Iron Man’s and Captain Marvel’s Anxieties and Defense Mechanisms in “Civil War II” - Lungky Saputro (Kata Kita: Journal of Language, Literature, and Teaching, 2018)
This thesis deals with the anxieties experienced by the leaders of superhero teams in Civil War II, Iron Man and Captain Marvel. Through their anxieties in Civil War II, I tried to reveal the causes of their anxieties and their ways to reduce these uneasy feelings. To analyze the causes of these two characters’ anxieties, I used two of the theory of anxiety, reality and moral anxiety. I found that there are two causes that make Iron Man feel anxieties which are the reaction of Captain Marvel towards Ulysses’ prophecies and his responsibility both as a superhero and as a leader to protect people from the outcome of Ulysses’ prophecies. On the other hand, Captain Marvel also feels anxieties from the blame of Iron Man and her responsibility both as a superhero and as a public officer to protect people from dystopian future. Iron Man uses two defense mechanisms, which are splitting and rationalization. On the other hand, Captain Marvel also uses two defense mechanism, which are idealization and rationalization. These defense mechanisms are used by both, Iron Man and Captain Marvel to ease their reality and moral anxiety.